Comparative transcriptomic analysis of two Saccharopolyspora spinosa strains reveals the relationships between primary metabolism and spinosad production - Yunpeng Zhang (Nature Portfolio, 2021)
Abstract Saccharopolyspora spinosa is a well-known actinomycete for producing the secondary metabolites, spinosad, which is a potent insecticides possessing both efficiency and safety. In the previous researches, great efforts, including physical mutagenesis, fermentation optimization, genetic manipulation and other methods, have been employed to increase the yield of spinosad to hundreds of folds from the low-yield strain. However, the metabolic network in S. spinosa still remained un-revealed. In this study, two S. spinosa strains with different spinosad production capability were fermented and sampled at three fermentation periods. Then the total RNA of these samples was isolated and sequenced to construct the transcriptome libraries. Through transcriptomic analysis, large numbers of differentially expressed genes were identified and classified according to their different functions. According to the results, spnI and spnP were suggested as the bottleneck during spinosad biosynthesis. Primary metabolic pathways such as carbon metabolic pathways exhibited close relationship with spinosad formation, as pyruvate and phosphoenolpyruvic acid were suggested to accumulate in spinosad high-yield strain during fermentation. The addition of soybean oil in the fermentation medium activated the lipid metabolism pathway, enhancing spinosad production. Glutamic acid and aspartic acid were suggested to be the most important amino acids and might participate in spinosad biosynthesis.